Interpretations of SARS-CoV-2 IgM and IgG antibody titers in the seroepidemiological study of asymptomatic healthy volunteers. Issue 2 (February 2022) - Mitani, Akihisa; Horie, Takeshi; Yokoyama, Rin; Nakano, Yuki; Hamada, Kensuke; Inoue, Yukiko; Saito, Minako; Ishii, Takashi; Sunohara, Mitsuhiro; Takahashi, Ryota; Usui, Tomoko; Emoto, Noriko; et al.
Abstract: Introduction: The usefulness of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody tests in asymptomatic individuals has not been well validated, although they have satisfied sensitivity and specificity in symptomatic patients. In this study, we investigated the significance of IgM and IgG antibody titers against SARS-CoV-2 in the serum of asymptomatic healthy subjects. Methods: From June 2020, we recruited 10, 039 participants to the project named the University of Tokyo COVID-19 Antibody Titer Survey (UT-CATS), and measured iFlash-SARS-CoV-2 IgM and IgG (YHLO IgM and IgG) titers in the collected serum. For the samples with increased IgM or IgG titers, we performed additional measurements using Elecsys Anti-SARS-CoV-2 Ig (Roche total Ig) and Architect SARS-CoV-2 IgG (Abbott IgG) and investigated the reactivity to N, S1, and receptor binding domain (RBD) proteins. Results: After setting the cutoff value at 5 AU/mL, 61 (0.61%) were positive for YHLO IgM and 104 (1.04%) for YHLO IgG. Few samples with elevated YHLO IgM showed reactivity to S1 or RBD proteins, and IgG titers did not increase during the follow-up in any samples. The samples with elevated YHLO IgG consisted of two groups: one reacted to S1 or RBD proteins and the other did not, which was reflected in the results of Roche total Ig. Conclusions: In SARS-CoV-2 seroepidemiological studies of asymptomatic participants, sufficient attention should be given to the interpretation of the results of YHLO IgM and IgG, and the combined use of YHLO IgG and Roche total Ig might be more reliable.